Examining Quitting Experiences on Quit Vaping Subreddits From 2015 to 2021: Content Analysis - Elexis Kierstead; Nathan Silver; Michael Amato (JMIR Publications, 2024)
BackgroundDespite the prevalence of vaping nicotine, most nicotine cessation research remains focused on smoking cigarettes. However, the lived experience of quitting smoking is different from quitting vaping. As a result, research examining the unique experiences of those quitting vaping can better inform quitting resources and cessation programs specific to e-cigarette use. Examining Reddit forums (ie, subreddits) dedicated to the topics of quitting vaping nicotine can provide insight into the discussion around experiences on quitting vaping. Prior literature examining limited discussions around quitting vaping on Reddit has identified the sharing of barriers and facilitators for quitting, but more research is needed to investigate the content comprehensively across all subreddits. ObjectiveThe objective of this study is to examine content across quit vaping subreddits since their inception to better understand quitting vaping within the context of the expanding nicotine market. MethodsAll posts from January 2015 to October 2021 were scraped from all quit vaping subreddits: r/QuittingJuul, r/QuitVaping, r/quit_vaping, and r/stopvaping (N=7110). Rolling weekly average post volume was calculated. A codebook informed by a latent Dirichlet allocation topic model was developed to characterize themes in a subsample of 695 randomly selected posts. Frequencies and percentages of posts containing each coded theme were assessed along with the number of upvotes and comments. ResultsPost volume increased across all subreddits over time, spiking from August - September of 2019 when vaping lung injury emerged. Just over 52% of posts discussed seeking social support and 16.83% discussed providing social support. Posts providing support received the most positive engagements (i.e. upvotes) of all coded categories. Posts also discussed physical and psychological symptoms of withdrawal (30.65% and 18.85%, respectively), strategies for quitting including: quitting cold turkey (38.33%), using alternative nicotine products (17%), and tapering down nicotine content (10.50%). Most posts shared a personal narrative (92.37%) and some discussed quit motivation (28.20%) and relapse (14.99%). ConclusionsThis work identifies a desire for peer-to-peer support for quitting vaping, which reinforces existing literature and highlights characteristics of quitting vaping specific to a changing nicotine product environment. Given that posts providing social support were the most upvoted, this suggests that subreddit contributors are seeking support from their peers when discussing quitting vaping. Additionally, this analysis shows the sharing of barriers and facilitators for quitting, supporting findings from prior exploration of quit vaping subreddits. Finally, quitting vaping in an ever-growing nicotine market has led to the evolution of vaping-specific quit methods such as tapering down nicotine content. These findings have direct implications for quit vaping product implementation and development.